EFEKTIVITAS MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS X IPA SMA NEGERI 1 KOLANG - eva wahyuni tanjung (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to know whether there is a significant effectiveness of using two stay two stray learning model on students’ mathematical communication ability at the tenth grade students of SMA Negeri 1 Kolang. The research was conducted by using experimental method with 35 students as the sample and they were taken by using cluster random sampling technique from74 students. Test and questionnaire were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using two stay two stray learning model was 3.51 (very good category), (b) before using two stay two stray learning model, the average of boys’ mathematical communication ability was 58.82 (less category) and girls’ mathematical communication ability was 57.17 (less category), and (c) after using two stay two stray learning model, the average of boys’ mathematical communication ability was 79.50 (good category) and girls’ mathematical communication ability was 82.50 (very good category). Furthermore, based on inferential statistic by using ttest (Pair Sample ttest), the result showed the significant value was less than 0.05 (0.000 <0.05. It is concluded two stay two stray learning model is effective to improve students’ mathematical communication ability at the tenth grade students of SMA Negeri 1 Kolang